A study on the relationship between motivation towards employee performance at Majlis Daerah Ketereh - Perbandaran Islam / Nor Hasliza Mohd@Mohamad - Mohd@Mohamad, Nor Hasliza (Faculty of Business and Management, 2019)
In a competitive business environment, the concept of motivation and employee performance has become a famous topic of discussion in many organizations. The organizations need to review their motivation that they give to their employees in order to improve employee performance and stay competitive. The purpose of this research was to investigate the relationship between motivation and employee performance. The research had the following three objectives: to identify the type of motivation that most affect employee performance, to determine the relationship between intrinsic motivation and employee performance, and to determine the relationship between extrinsic motivation and employee performance. The literature was reviewed based on the study objectives. The motivation were divided into two types which is intrinsic motivation and extrinsic motivation. It adopted a correlation survey research design. One hundred and thirteen (113) questionnaires were distributed to the employees at Majlis Daerah Ketereh - Perbandaran Islam in order to gain and examine their views on these issues. Questionnaires were used as the main tools for data collection. The instruments were tested for test reliability and normality through a pilot study through the public people that age 18 above. After that, the data was transferred using the statistical package for social sciences version 24.0 to process the data. The data was analyzed using a frequency distribution tables and percentages, mean and standard deviation and Pearson correlation. Based on the data collected, it can be concluded that the most affective motivation was intrinsic motivation. Based on the analysis of the collected data, the following recommendations were made: organization should focus on intrinsic motivation to increase employee performance, and use extrinsic motivation to reduce dissatisfaction. However, the organizations should identify the most important motivational factor as preferred by the employees to meet employee needs.